2015
DOI: 10.1111/jnc.13225
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Insulin receptor A and Sirtuin 1 synergistically improve learning and spatial memory following chronic salidroside treatment during hypoxia

Abstract: Hypoxia has been reported to cause hippocampal neurodegeneration resulting in learning and memory deficits. In the present study, we investigated the potential of salidroside, a glucoside derivative of tyrosol, in ameliorating hypoxia-induced neurodegeneration and memory impairment. Morris water maze test showed improvement in learning and spatial memory of salidroside-treated hypoxic rats correlating with increased dendritic intersections and arborization. Salidroside administration increased phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 69 publications
0
43
0
Order By: Relevance
“…Insulin interaction with the AMPK pathway is multifaceted (Towler and Hardie, 2007) and adipocytes maintained under conditions of ongoing fatty acid metabolism, insulin can activate AMPK over a period of 40 min via elevation in the AMP/ATP ratio (Hebbachi and Saggerson, 2012; Liu et al, 2010). In hippocampal neurons, compounds that activate the insulin receptor also mobilize the AMPK-SIRT signaling axis with associated enhancement of mitochondrial function (Barhwal et al, 2015). Insulin can also boost intracellular Ca 2+ ion concentration (Contreras-Ferrat et al, 2014) which could trigger activation of an upstream activator of AMPK, namely Ca 2+ /calmodulin-dependent protein kinase kinase β (CaMKKβ) (Hawley et al, 2005; Hurley et al, 2005; Woods et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin interaction with the AMPK pathway is multifaceted (Towler and Hardie, 2007) and adipocytes maintained under conditions of ongoing fatty acid metabolism, insulin can activate AMPK over a period of 40 min via elevation in the AMP/ATP ratio (Hebbachi and Saggerson, 2012; Liu et al, 2010). In hippocampal neurons, compounds that activate the insulin receptor also mobilize the AMPK-SIRT signaling axis with associated enhancement of mitochondrial function (Barhwal et al, 2015). Insulin can also boost intracellular Ca 2+ ion concentration (Contreras-Ferrat et al, 2014) which could trigger activation of an upstream activator of AMPK, namely Ca 2+ /calmodulin-dependent protein kinase kinase β (CaMKKβ) (Hawley et al, 2005; Hurley et al, 2005; Woods et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In present study, we found that MPP + treatment obviously decreased the SIRT1 activity, SIRT1 mRNA and protein levels in SH‐SY5Y cells, which is also consistent with the research done by Dong et al (), Tao et al (), and Zou et al (). Remarkably, some researchers reveal that SIRT1 contributes to the protective effects of salidroside against kainic acid‐induced status epilepticus (Si et al, ), d ‐galactose‐induced rat model of Alzheimer's disease (AD) (Gao et al, ), and hypoxia‐induced neurodegeneration (Barhwal et al, ). However, the role of SIRT1 in salidroside‐induced neuroprotection against injury in PD was not yet explored.…”
Section: Discussionmentioning
confidence: 99%
“…MPP+ also stimulates the release of DA [119], and autooxidation of dopamine results in the formation of cytotoxic quinones and highly reactive hydroxyl radicals, generating biomolecular damage [120]. In contrast to this, neuroprotection CYP2E1-regulated mechanism has been observed in a hypoxia model [121]. …”
Section: Cyp2e1 Relationship With Brain Disordersmentioning
confidence: 99%